Assessing drought variability since 1650 AD from tree‐rings on the Jade Dragon Snow Mountain, southwest China - Yingfeng Bi; Jianchu Xu; Aster Gebrekirstos; Liang Guo; Mingxu Zhao; Eryuan Liang; Xuefei Yang (International Journal of Climatology, 2015)
Southwest China has experienced significant drought during the past few years. To better understand the tendency of drought changes over time, this study applies dendroclimatological techniques to assess drought variations in Lijiang Prefecture, southwest China. So far, the longest chronology (387 years) of Picea likiangensis on the Jade Dragon Snow Mountain was constructed, and the relationships between the tree‐ring width and climate variables were analysed. The spring season Palmer Drought Severity Index ( PDSI ) was reconstructed based on a standard chronology. Tree‐ring width is positively related to precipitation and relative humidity from February to March and the PDSI from January to May. Conversely, tree‐ring width is also negatively related with mean temperature from January to May, suggesting that growth of P. likiangensis is affected both by temperature and precipitation. The reconstructed PDSI showed that the Jade Dragon Snow Mountain has experienced considerable variations in spring drought conditions during the past 361 years. Four distinct periods were recognized: (1) 1650–1730, a relatively humid period with an average PDSI value above zero; (2) 1730–1860, a period with greatly fluctuating PDSI and intermittent wet periods (1746–1755, 1782–1800, and 1820–1830) and several dry periods (1735–1745, 1756–1780, 1810–1820, and 1830–1860); (3) 1870–1945, a humid period, with the highest PDSI value during 1930–1945; and (4) 1945–2011, a period with decreasing humidity. The results are consistent with hydrological studies in nearby regions and related species, as well as historical records of natural disasters. The recently observed spring drought follows a trend of decreasing humidity over the past 60 years, suggesting that a sound strategy for management and land‐use planning is required to secure ecosystem and human well‐being.